Sports and Exercise Medicine in India: Looking Beyond Injury - Hanjabam Barun Sharma (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
Sports Medicine (SM) is a new specialty in India which has been often projected, dealing only with treating musculoskeletal (MSK) sports injuries. With adequate training in medical and clinical physiology, SM physicians have an important role to play as an essential part of the multidisciplinary and multispecialty team in the fight against the rise of physical inactivity, sedentary lifestyle and non-communicable diseases. Dope-free sports performance enhancement is another important aspect, which needs beyond the MSK centric approach of sports medicine. There is need for awareness and overall development of this unique specialty, with contribution from government side and non-government organizations.